STORE ATMOSPHERE DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN PADA RESTORAN KAPAL JODOH BATU MARMAR PAMEKASAN - Riskiyah, Nuer; Kunaifi, Aang; Matnin, Matnin; Asyari, Qaiyim (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2020)
The purpose of this study was conducted with the main objective to be achieved, namely to determine the store atmosphere and purchase decisions at the Jodoh Tamberu Alet Ship Restaurant, Batu Marmar District. Atmospheric refreshes to the store's physical characteristics that are used to develop an image and to draw customers, which means that a cafe atmosphere is a physical characteristic used to build an impression and to attract customers. The elements of the atmosphere can be operationalized in the restaurant as objects in this study, namely: Layout, sound, smell, texture, building design. The study will contain data quotations to provide an overview of the presentation of the report. The data may come from manuscripts of interviews with owner and management, field notes, photos, notes or memos directly from the location. Data collection procedures used in this study were interviews, observation and documentation. The analysis used in this research is non-statistical analysis. This study analyzes data from interviews, observations, and documentation. The stages of analysis carried out by researchers in this study are as follows: Reduction, Display, Conclusion drawing. Based on literature review, the results of field research and data analysis, the researcher can conclude that the store atmosphere in the form of layout, sound, smell, texture and building design in a restaurant has an impact in increasing purchasing decisions on matchmaking vessels. This is because consumers tend to enjoy the restaurant atmosphere other than just enjoying food.